Phenotypical variability and atypical presentations in a French cohort of Andersen–Tawil syndrome. (4th May 2022) - Villar‐Quiles, Rocio Nur; Sternberg, Damien; Tredez, Grégoire; Beatriz Romero, Norma; Evangelista, Teresinha; Lafôret, Pascal; Cintas, Pascal; Sole, Guilhem; Sacconi, Sabrina; Bendahhou, Said; Franques, Jérôme; Cances, Claude; et al.
Abstract: Background and purpose: Andersen–Tawil syndrome (ATS) is a skeletal muscle channelopathy caused by KCNJ2 mutations, characterized by a clinical triad of periodic paralysis, cardiac arrhythmias and dysmorphism. The muscle phenotype, particularly the atypical forms with prominent permanent weakness or predominantly painful symptoms, remains incompletely characterized. Methods: A retrospective clinical, histological, electroneuromyography (ENMG) and genetic analysis of molecularly confirmed ATS patients, diagnosed and followed up at neuromuscular reference centers in France, was conducted. Results: Thirty‐five patients from 27 unrelated families carrying 17 different missense KCNJ2 mutations (four novel mutations) and a heterozygous KCNJ2 duplication are reported. The typical triad was observed in 42.9% of patients. Cardiac abnormalities were observed in 65.7%: 56.5% asymptomatic and 39.1% requiring antiarrhythmic drugs. 71.4% of patients exhibited dysmorphic features. Muscle symptoms were reported in 85.7%, amongst whom 13.3% had no cardiopathy and 33.3% no dysmorphic features. Periodic paralysis was present in 80% and was significantly more frequent in men. Common triggers were exercise, immobility and carbohydrate‐rich diet. Ictal serum potassium concentrations were low in 53.6%. Of the 35 patients, 45.7% had permanent weakness affecting proximal muscles, which was mild and stable or slowly progressive over several decades. Four patients presented with exercise‐induced pain and myalgia attacks. Diagnostic delay was 14.4 ± 9.5 years. ENMG long‐exercise test performed in 25 patients (71.4%) showed in all a decremental response up to 40%. Muscle biopsy performed in 12 patients revealed tubular aggregates in six patients (associated in two of them with vacuolar lesions), dystrophic features in one patient and non‐specific myopathic features in one patient; it was normal in four patients. Discussion: Recognition of atypical features (exercise‐induced pain or myalgia and permanent weakness) along with any of the elements of the triad should arouse suspicion. The ENMG long‐exercise test has a high diagnostic yield and should be performed. Early diagnosis is of utmost importance to improve disease prognosis. Abstract : Retrospective analysis of 35 molecularly confirmed ATS patients. The typical triad was observed in 42.9%. Cardiac abnormalities were observed in 65.7%. 71.4% exhibited dysmorphic features. Muscle symptoms were reported in 85.7%: 13.3% had no cardiopathy and 33.3% no dysmorphic features. PP was present in 80%, more frequent in men. Common triggers were exercise, immobility, and carbohydrate‐rich diet. Ictal serum potassium was low in 53.6%. 45.7% patients had permanent mild proximal weakness. Atypical presentations included exercise‐induced pain and myalgia attacks. ENMG long exercise test is a high‐yield diagnostic tool. Muscle biopsy revealed tubular aggregates, vacuolar lesions, dystrophic and non‐specific features.